THE EXPRESSIVE SPEECH ACT USED BY ANIES RASYID BASWEDAN AND RECEP TAYYIP ERDOGAN AS THE REACTION OF THE ATTACKS IN CHRISTCHURCH NEW ZEALAND - Badrut Tamam; Slamet Setiawan; Syafiul Anam (Prasasti: Journal of Linguistics)
This study attempts to compare between Anies Rasyid Baswedan and Recep Tayyip Erdogan in terms of speech act as their reaction of the attacks in Christchurch New Zealand particularly: a) the kinds of expressive speech act used; b) the intended meaning of expressive speech act; and c) the personality differences between them seen the use of speech act. The qualitative method was used to fulfil the three objectives of the study. The data was collected from document that was taken from the utterances used by the two public figures. It was transcribed and then analysed descriptively. The results show that the speakers used three kinds of expressive speech acts, namely: condoling, deploring, and lamenting. Condoling is an expressive speech acts were mostly used to communicate by the speakers. The intended meaning of expressive speech act used by the speakers are determined by interpreting and determining what speakers means in the context. In addition, the personality characters of Anies Rasyid Baswedan are kind, clever, and soft, whereas, the personality characters of Recep Tayyip Erdogan are courageous, influential person, and clever.